Adoption incentives and environmental policy timing under asymmetric information and strategic firm behaviour - D'Amato, Alessio; Dijkstra, Bouwe (Springer Verlag, 2017)
We consider the incentives of a single firm to invest in a cleaner technology under emission quotas and emission taxation. We assume asymmetric information about the firm's cost of employing the new technology. Policy is set either before the firm invests (commitment) or after (time consistency). Contrary to conventional wisdom, we find that with commitment (time consistency), quotas give higher (lower) investment incentives than taxes. With quotas (taxes), commitment generally leads to higher (lower) welfare than time consistency. Under commitment with quadratic abatement costs and environmental damages, a modified Weitzman rule applies and quotas usually lead to higher welfare than taxes.